Becoming French in School: Memories of School Life in Chemin D’école by Patrick Chamoiseau - Hayuningsih, Arifah Arum Candra (Lingua Cultura, 2024)
The research explored the theme of ‘becoming French’ in the novel Chemin d'école by Patrick Chamoiseau. The novel offered a unique perspective on the complex issues of identity, language, and colonial legacy within the Caribbean educational context. The central focus of the research was to examine how the mission civilisatrice was implemented through the education system in the French colonies. The French mission civilisatrice aimed to ‘civilize’ the colonies, exerting influence over the lives of children within these territories. In this postcolonial narrative, Chamoiseau challenged the erasure of Creole culture and identity as children were molded into the French mold. His work underscored the tension between the native language and the French language, serving as a commentary on linguistic and cultural colonialism. Incorporating Frantz Fanon’s theoretical framework from “Black Skin, White Masks”, the research illuminated colonialism’s psychological and cultural impacts, revealing the enduring consequences of internalized racism and the complexities of ‘becoming French’ in a postcolonial context. A qualitative research design utilizing literary analysis was applied, involving systematic reading and coding of Chamoiseau’s novel. The findings suggest that through its portrayal of the education system, language erasure, and cultural identity, the novel offers a poignant and thought-provoking narrative that illuminates the process of ‘becoming French’ in a postcolonial context, providing insights into the challenges and complexities faced by individuals subjected to the mission of French civilization.